LMI-based robust control of uncertain nonlinear systems via polytopes of polynomialsLMI-based robust control of uncertain nonlinear systems via polytopes of polynomials - Sánchez, Marcelino; Bernal, Miguel (Zielona Góra: Uniwersytet Zielonogórski)
This investigation is concerned with robust analysis and control of uncertain nonlinear systems with parametric uncertainties. In contrast to the methodologies from the field of linear parameter varying systems, which employ convex structures of the state space representation in order to perform analysis and design, the proposed approach makes use of a polytopic form of a generalisation of the characteristic polynomial, which proves to outperform former results on the subject. Moreover, the derived conditions have the advantage of being cast as linear matrix inequalities under mild assumptions.
Keywords: robust control; uncertain systems; nonlinear systems; linear parameter-varying systems; LMIs